KOTAK LITERASI SEBAGAI ALAT PERMAINAN EDUKATIF DALAM MENINGKATKAN LITERASI ANAK USIA DINI MELALUI PEMBELAJARAN TER DIFERENSIASI - Raoda Tul Jannah Maruddani; Kaspul Anwar; Fitriah; Melviana Safitri (LP2M IAIN Sultan Amai Gorontalo, 2025)
This research is motivated by the problem of literacy skills of children aged 5-6 years at Roudhotu Ash Shibyan Kindergarten, Jambi City. The number of students at Roudhotu Ash Shibyan Kindergarten is 15 children, 5 boys and 10 girls. Based on the results of initial observations, it was found that the development of children's literacy skills had not developed well. The research method used in this study is PTK, the purpose of Classroom Action Research (PTK) is to improve the quality and learning outcomes practically. Classroom action research focuses on the class or on the learning process that occurs in the classroom. The results of the study showed that the literacy skills of children aged 5-6 years at Roudhotu Ash Shibyan Kindergarten in Jambi City increased using educational literacy box game tools with differentiated learning, this is evidenced by the end of cycle II action III that the scope of development of the basics of literacy with a description of the achievements of children's development is able to listen, have awareness of text messages, alphabets, and phonemics, are able to express questions and ideas, are able to use their language for cooperation skills, so there are no children who are BB (Not Yet Developing), there are no children who are MB (Starting to Develop), children who are BSH (Developing According to Expectations) are 20%, children who are BSB (Developing Very Well) are 80%